2023
DOI: 10.3390/brainsci13060901
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Awareness Levels of Individuals with Alcohol and Substance Use Disorders: Tertiary Prevention Standards and Development of Uskudar Result Awareness and Harm Perception Scales

Abstract: Rationale: Alcohol and substance use disorders are types of brain diseases that have psychological components which damage many life areas of the affected individual. Since investigating alcohol use alone is insufficient in the diagnostic evaluation process, self-awareness and the individual’s long-term psychological well-being are important in the treatment process. Primary prevention is used for preventing disease in healthy people, whereas secondary prevention is used for early diagnosis of people at risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Factor analysis is a dimensionality reduction method carried out by grouping variables that have a common meaning [ 86 , 87 ]. To determine the suitability of the data for the application of factor analysis, two tests were conducted [ 88 ]: (a) the Kaiser–Meyer–Olkin (KMO) test was used to assess the adequacy of the sample [ 89 ] and (b) Bartlett’s test of sphericity was used to determine whether the variables are sufficiently correlated in the correlation matrix [ 90 ]. A loading value of 0.70 was considered substantial for each factor selection [ 91 ], and Cattell’s Scree Test was used to determine the number of factors [ 92 , 93 ].…”
Section: Methodsmentioning
confidence: 99%
“…Factor analysis is a dimensionality reduction method carried out by grouping variables that have a common meaning [ 86 , 87 ]. To determine the suitability of the data for the application of factor analysis, two tests were conducted [ 88 ]: (a) the Kaiser–Meyer–Olkin (KMO) test was used to assess the adequacy of the sample [ 89 ] and (b) Bartlett’s test of sphericity was used to determine whether the variables are sufficiently correlated in the correlation matrix [ 90 ]. A loading value of 0.70 was considered substantial for each factor selection [ 91 ], and Cattell’s Scree Test was used to determine the number of factors [ 92 , 93 ].…”
Section: Methodsmentioning
confidence: 99%
“…While human beings became richer materially, they became poorer emotionally and began to harm those around them. Nowadays, many problems such as alcohol, tobacco, substance use, behavioral addictions, psychological disorders, communication and relational problems, inability to maintain a healthy family life, exhibiting wrong parenting attitudes and behaviors, resorting to physical or emotional violence, and suicide are rapidly spreading around the world like a virus [1][2][3][4][5][6][7] . It is reported that negative emotions that exist in the body for a long time and distorted, harmful, unbalanced relationship patterns threaten human health [8] .…”
Section: Introductionmentioning
confidence: 99%